Estimates Committee 1957-58 Sixteenth Report (Second Lok Sabha) Ministry of Education and Scientific Research - Ministry Of Education and Scientific Research (Ministry Of Education and Scientific Research, 1958)
The National Archives of India which is the repository of the non-current records of the Government of India was set up in 1891 at Calcutta under the name of the Imperial Record Department. After the transfer of the Capital from Calcutta to New Delhi in 1911, the records of the Government were also gradually transferred to New Delhi between the years 1926 and 1937. In 1947 the Department was renamed as the National Archives of India.
Ministry Of Education and Scientific Research
Ministry Of Education and Scientific Research